Field programmable gate array implementation of edge detection system based on an improved sobel edge detector - Duong Huu Ai; Cong Dat Vuong; Khanh Ty Luong; Viet Truong Le (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Field programmable gate array (FPGA) is an integrated circuit consisting of internal hardware blocks with programmable link connections for users to customize operations for a particular application. Link connections can be easily reprogrammed, allowing the FPGA to adapt to changes to the design or even support a new application throughout the department's uptime. One of the important tasks in image processing is image edge detection image, with computer aided, image recognition is concerned with the recognition and classification of objects in an image, so edge detection is an important tool. In this paper, we design filter for edge detection in image processing using FPGA kit. We analysis and implementation of algorithm for image processing on FPGA, load the code and run the results. Comparative analysis with images processed by MATLAB software.